E-Learning For Life - With A Difference. - Ayob, Aminah; Mohamed, Abdul Rashid (2004)
This is a project jointly sponsored by the Malaysian Ministry of Education, United Nation Development Programme, and Coca-cola Far East Limited. The specific objectives of the project were to: Set up and equip six hub schools in rural areas of the Peninsular Malaysia, with physical ond technical infrastructure and facilities;